DISTRIBUTION OF METALS IN BOTTOM DEPOSITS IN THE BRANCHES OF SELENGA RIVER DELTA - Khazheeva Z.I.; Tulokhonov A.K. (My University, 2007)
The paper reports newly obtained data on the granulometric and mineralogical composition of bottom deposits in branches in the Selenga River delta and on the distribution of metals in various granulometric fractions and along the length of an branch of the river in the delta. It was determined that carbonates precipitate as a solid phases in the Kharauz branch, the most copious stream in the delta, and the metals are concentrated in the sand fraction. The bottom deposits of the minor Kolpinnaya branch are characterized by the accumulation of Mn oxides of variable composition, a mixture of colloidal or poorly crystalline minerals (most commonly, pyrolusite). Most of the metals are concentrated in the pelite fraction. © Pleiades Publishing, Ltd. 2007.